Reading Materials Development through Task-Based Language Instruction Approach for Business Administration Students - Citra Hasan; Busmin Gurning; Amrin Saragih (LINGUISTIK TERAPAN, 2015)
This research aims to develop the materials of reading by conducting need analysis in order to meet the needs of business administration students. The method of research was a research and development (R&D) by Borg and Gall which are modified in to three main cycles, namely: evaluation and needs assessment, materials development, and materials validation. The study found that the existing materials of reading II are not match with the needs analysis result. Thus, the researcher added 13 more basic competencies of the syllabus and materials of reading related to the learners needs and learning needs. Keywords: Business English; Materials; Reading; Task-Based Language Instruction Approach